2022
DOI: 10.25222/larr.191
|View full text |Cite
|
Sign up to set email alerts
|

Mexicans and Colombians at Home and Abroad: A Comparative Study of Political Engagement

Abstract: Although a large number of democracies have extended political rights to expatriates, relatively little is known about the depths of transnational political engagement. How attentive are expatriates to politics in the country of origin? When expatriates judge leaders "back home," are their evaluations based on the same ideological considerations as those of citizens in the country of origin? Drawing from original surveys conducted during presidential elections in Mexico (2006) and Colombia (2010), in which bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(40 reference statements)
1
5
0
2
Order By: Relevance
“…These findings confirm what McCann et al. (2019) proposed regarding the non‐diminishment of potential democratic engagement when it existed in the country of origin.…”
Section: What Explains the Electoral Participation Of Migrants?supporting
confidence: 90%
“…These findings confirm what McCann et al. (2019) proposed regarding the non‐diminishment of potential democratic engagement when it existed in the country of origin.…”
Section: What Explains the Electoral Participation Of Migrants?supporting
confidence: 90%
“…The country of birth and the length of residency in the host country also play a role (Peltoniemi, 2018;Szulecki et al, 2021): studies point to a decline in participation with length of residence abroad (Belchior et al, 2018;Waldinger, 2012). Studies show that interest in home country politics as well as previous political experience in the home country increases the likelihood of voting (Lafleur & Chelius, 2011;McCann et al, 2019;McIlwaine & Bermudez, 2015;Peltoniemi, 2018), yet higher cost of voting (distance to polling station (Peltoniemi, 2018), and higher perceived cost of voting, decrease the probability to vote & Bermudez, 2015;Wass et al, 2021), confirming findings at the aggregate level. Participation in homeland elections is also driven by a sense of duty, patriotism, homesickness, and a desire to reproduce a social milieu abroad (Boccagni, 2011;Boccagni & Ramirez, 2013;Knott, 2017;McCann et al, 2019).…”
Section: Studying Parties Abroadmentioning
confidence: 99%
“…Similarly, several studies have suggested that non-resident citizens' voter turnout is partly influenced by prior political socialization (pre-emigration) (e.g., Boccagni, 2011;Lafleur & Sánchez-Domínguez, 2015;McCann et al, 2019). Given that civic duty to vote precedes adulthood and might be fostered by political socialization in the family and at school Feitosa et al, 2022;Galais, 2018), pre-emigration political socialization may explain why some countries exhibit relatively high rates of non-resident citizens' voter turnout even if only resident citizens are obliged to vote.…”
Section: Compulsory Voting and Non-resident Citizens' Voter Turnoutmentioning
confidence: 99%
“…Burgess & Tyburski, 2020;Ciornei & Østergaard-Nielsen, 2020) or individual level (e.g. Chaudhary, 2018;Himmelroos & Vento, 2022;Lafleur & Sánchez-Domínguez, 2015;McCann et al, 2019;Mügge et al, 2021;Peltoniemi, 2018). Earlier research has connected non-resident citizens' voter turnout to (in)formal channels of sociopolitical activism across borders, the activities of political parties abroad, the role of migrant civic associations, the voting methods and the characteristics of electoral districts abroad (e.g.…”
Section: Introductionmentioning
confidence: 99%